One ‘P’ to Conquer them all: An existential-phenomenological critique of the ‘5 P s model’ of psychological formulation and its alternative (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
The present paper will provide an overview of the concept of psychological formulation, by providing a critique of Weerasekera's (1996) '5 Ps model' and through presenting a phenomenological alternative, which addresses the inherent limitations of Weerasekera's approach. Consideration is also given to the effects upon the therapeutic relationship and process of each model.
Keywords: Formulation; existential; phenomenology; noetic; relational; Being-in- the-world